2019
DOI: 10.7150/thno.32867
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Promotes Photodynamic Therapy: Supramolecular Photosensitizer-Inducer Nanodrug for Enhanced Cancer Treatment

Abstract: The noninvasive nature of photodynamic therapy (PDT) enables the preservation of organ function in cancer patients. However, PDT is impeded by hypoxia in the tumor microenvironment (TME) caused by high intracellular oxygen (O 2 ) consumption and distorted tumor blood vessels. Therefore, increasing oxygen generation in the TME would be a promising methodology for enhancing PDT. Herein, we proposed a concept of ferroptosis-promoted PDT based on the biochemical characteristics of cellular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(137 citation statements)
references
References 42 publications
1
135
0
1
Order By: Relevance
“…Cell death was defined in many variations 45 . It has been reported that various cell death such as autophagy, necroptosis and ferroptosis were induced by PDT [46][47][48][49] . Future studies will need to investigate the details of cell death by ALA-PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death was defined in many variations 45 . It has been reported that various cell death such as autophagy, necroptosis and ferroptosis were induced by PDT [46][47][48][49] . Future studies will need to investigate the details of cell death by ALA-PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitizer chlorin e6 (Ce6) and the ferroptosis inducer erastin were self-assembled into a novel supramolecular Ce6-erastin nanodrug though bonding and π−π stacking. Ferroptosis with nanodrug enhances anticancer actions by relieving hypoxia and promoting ROS production [ 140 ].…”
Section: Cancer Therapymentioning
confidence: 99%
“…Ferroptosis-inducing factors can directly or indirectly affect glutathione biosynthesis or the glutathione-dependent antioxidant enzyme glutathione peroxidase 4 (GPX4) resulting in a decrease in antioxidant capacity and accumulation of lipid-RMS (singlet oxygen) in cells, ultimately leading to oxidative cell death, which is marked by the depletion of plasma membrane polyunsaturated fatty acids. A few reports have highlighted PDT associated ferroptosis [82,131,132] in different tumor models and is usually observed when specific PSs are used in the PDT process. Turubanova et al, using photosens and photodithazine as PSs, demonstrated inhibition of cell death when ferrostatin-1 (ferroptosis inhibitor) was used in photosens-mediated PDT, highlighting the occurrence of ferroptosis mediated cell death [82].…”
Section: Subcellular Localization and Cell Death Pathways Associated mentioning
confidence: 99%
“…Turubanova et al, using photosens and photodithazine as PSs, demonstrated inhibition of cell death when ferrostatin-1 (ferroptosis inhibitor) was used in photosens-mediated PDT, highlighting the occurrence of ferroptosis mediated cell death [82]. Another recent study [131] suggests that ferroptosis could enhance PDT efficacy by maintaining a sustainable O 2 supply (generated through the Fenton reaction). Moreover, the additive effect of lipid-RMS, generated by ferroptosis, and ROS generated by PDT, could potentially enhance cytotoxicity even in tumors where the associated hypoxia is often the cause of low PDT efficacies.…”
Section: Subcellular Localization and Cell Death Pathways Associated mentioning
confidence: 99%